Utilization of Digital Technology as A 21st Century Learning Innovation - Taqiyya, Wafa; Haryanto, Sigit (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the use of digital technology in the context of 21st century learning innovation, focusing on aspects of educational management and administration. Using a literature study approach, this study examines various national and international literature related to 21st century skills (4C), digital literacy, Learning Management System (LMS), and innovative learning models. The results of the study indicate that the integration of digital technology has a positive impact on learning effectiveness, increasing student participation, and efficiency of educational administration. In addition to pedagogical aspects, the success of digital transformation is greatly influenced by infrastructure readiness, educator competence, and school leadership and policies. The main challenge is found in the form of a digital divide between urban and 3T (underdeveloped, leading, and outermost) areas. This study offers a systemic approach to managing digital learning and suggests the need for cross-sector collaboration to create an adaptive, inclusive, and sustainable education ecosystem.